Ultrasound guided hydrostatic reduction of intussusception: suitability and effectiveness with factors affecting its successful outcome - Shiekh, Yassar; Khan, Aamir Javed; Bhawani, Shafqat Shabir (International Journal of Advances in Medicine, 2019)
Background: Intussusception being the leading cause of acute abdomen in childhood, its timely and accurate diagnosis assumes utmost significance in reducing the morbidity and mortality. Childhood intussusceptions are still managed surgically in our region; however, non-operative reduction has now become the gold standard of treatment worldwide. In this study, authors desired to evaluate the suitability and effectiveness of hydrostatic reduction of intussusception under ultrasound (USG)-guidance and to scrutinize the factors affecting the successful outcome. Methods: Ours was a prospective study carried out at a tertiary care centre in central Kashmir. All except those with clinical features of bowel gangrene, intestinal prolapse and peritonitis underwent ultrasound-guided hydrostatic reduction (USGHR). A maximum of three attempts were allowed. Results: Mean age of the patients was 11.2±8.8 months with age range of 3-50 months. 69.1% (n=38) of the patients presented within 24 h of being symptomatic while 30.9% had delayed presentation (>24 h). The success rate of USGHR was 81.8% (n=45). Late presentation, age and gender of the patients had no influence on successful outcome of the procedure, p >0.005. The duration of hospital stay between those who had successful hydrostatic reduction and those who afterwards underwent operative reduction or resection achieved statistical significance, p=0.0015. Authors attained a 66.2 % (45/68) reduction in operative management using USGHR as the main modality of treatment. Conclusions: USGHR is a simple, safe and effective non-operative method of treating intussusceptions in children in a limited resource setting.